1997
DOI: 10.1146/annurev.pharmtox.37.1.143
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Farnesyltransferase Inhibitors as Cancer Chemotherapeutics

Abstract: Mutant ras oncogenes and alterations in the mitogenic signaling pathways that they regulate are associated with a wide variety of solid tumors and leukemias for which existing chemotherapeutics have limited utility. Of the possible approaches to inhibit Ras function, much attention has focused on a posttranslational modification, farnesylation, which is required for the subcellular localization of Ras to the plasma membrane and is critical to Ras cell-transforming activity. Inhibitors of the enzyme that cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
200
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(202 citation statements)
references
References 108 publications
2
200
0
Order By: Relevance
“…Farnesyltransferase (FTase) and geranylgeranyltransferase I (GGTase) inhibitors (FTIs and GGTIs) are novel classes of antitumor agents whose development was based upon the discovery that post-translational prenylation is required for the oncogenic properties of some GDP/GTP binding GTPases such as Ras and Rho (Cox and Der, 1997;Gibbs and Oliff, 1997;Sebti and Der, 2003). Protein prenylation involves C-terminal addition of C15 (farnesyl) by FTase or C20 (geranylgeranyl) by GGTase I (Zhang and Casey, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Farnesyltransferase (FTase) and geranylgeranyltransferase I (GGTase) inhibitors (FTIs and GGTIs) are novel classes of antitumor agents whose development was based upon the discovery that post-translational prenylation is required for the oncogenic properties of some GDP/GTP binding GTPases such as Ras and Rho (Cox and Der, 1997;Gibbs and Oliff, 1997;Sebti and Der, 2003). Protein prenylation involves C-terminal addition of C15 (farnesyl) by FTase or C20 (geranylgeranyl) by GGTase I (Zhang and Casey, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…FTIs and GGTIs are potent inhibitors of Ras and Rho processing, respectively, and suppress the growth of murine and human tumors in various animal models (Kohl et al, 1994;Nagasu et al, 1995;Barrington et al, 1998;Liu et al, 1998;Sun et al, 1998;Hunt et al, 2000). Recent investigations into the biological mechanisms that underlie FTI anti-transforming effects have raised questions about their exact mode of action (Cox and Der, 1997;Gibbs and Oliff, 1997;Sebti and Hamilton, 2000;Sebti and Der, 2003). For example, there was no correlation between the Ras mutation status and reversal of transformation as some cancer cells that do not express oncogenic Ras were sensitive to FTI, and inversely, some cancer cells containing activated Ras were resistant to FTI (Cox and Der, 1997;Gibbs and Oliff, 1997;Sebti and Hamilton, 2000;Sebti and Der, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 When Âźrst evaluated, it was felt that these agents might be best suited for tumors harboring mutant Ras genes. In an earlier study, we showed, however, that these compounds inhibited the growth of human cancer lines, including prostate, in which Ras mutations are rarely found.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In cultured human tumor cells, SCH-66336 effectively inhibits the isoprenylation of H-Ras but not of K-or N-Ras as these proteins can be alternatively lipidated by GGTase I. 5 Furthermore, SCH-66336 reduces activated, GTP-bound Ras levels, 6 suggesting that pathways downstream of Ras are perturbed by the FTI.…”
mentioning
confidence: 99%